About Uzbek Opera (Zien Journal of Social Sciences and Humanities, 2022)
This article is about Uzbek opera. Artists of the Russian Opera House began to promote the art of opera among the Uzbek people by organizing performances in the regions of Uzbekistan and these services became the basis for the creation of Uzbek operas.